What can we learn from the Baduanjin rehabilitation as COVID‐19 treatment?: A narrative review - Zhenggang Zhu; Xiaoyan Pan; Faping Zhong; Jun Tian; Marilyn Li Yin Ong (Wiley, 2023)
Abstract Aim To understand Baduanjin rehabilitation therapy in mild COVID‐19 patients. Design A narrative review. Methods A literature search for COVID‐19 and Baduanjin treatments was conducted on Chinese and English electronic databases: China National Knowledge Infrastructure, Wanfang Data, Embase, PubMed, Scopus, Science Direct, Ebscohost, SPORTDiscus and ProQuest. Results Twelve studies on the Baduanjin rehabilitation for COVID‐19 patients have been included. We acknowledged the considerable published research and current clinical practice using Baduanjin for COVID‐19 treatment in the following areas: anxiety, depression, insomnia, lung function rehabilitation, immunity and activity endurance. Conclusion The use of Baduanjin as adjuvant therapy for COVID‐19 patients' rehabilitation is still limited, therefore, more clinical studies are needed to confirm its efficacy.